2021
DOI: 10.1007/s11207-021-01770-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Accelerating Solar Eruptions Using Parabolic Hough Transform

Abstract: Solar eruptions such as Coronal Mass Ejections (CMEs) observed in the inner solar corona (up to 4 R ) show acceleration profiles which appear as parabolic ridges in height-time plots. Inspired by the white-light automated detection algorithms, Computer Aided CME Tracking System (CACTus) and So-R.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Inspired by the WL automated-detection algorithms of CACTus and SEEDS, Patel et al (2021) used the large FOV of SWAP, along with EUVI and AIA observations to build and test an automated-tracking algorithm, CME Identification in Inner Solar Corona (CIISCO), that uses Fourier motion filtering and the parabolic Hough transform for the first time to automatically detect off-disk solar eruptions in the lower and middle corona. The Hough transform is suited to tracking the kinematic profiles of eruptions in their initiation and impulsive phases.…”
Section: Automatically Detecting Eruptionsmentioning
confidence: 99%
“…Inspired by the WL automated-detection algorithms of CACTus and SEEDS, Patel et al (2021) used the large FOV of SWAP, along with EUVI and AIA observations to build and test an automated-tracking algorithm, CME Identification in Inner Solar Corona (CIISCO), that uses Fourier motion filtering and the parabolic Hough transform for the first time to automatically detect off-disk solar eruptions in the lower and middle corona. The Hough transform is suited to tracking the kinematic profiles of eruptions in their initiation and impulsive phases.…”
Section: Automatically Detecting Eruptionsmentioning
confidence: 99%
“…The main impulsive acceleration phase however, is qualitatively very different from the initial slow rise phase and involves a rapid increase in acceleration in a short interval of time, that shoots the CMEs to high velocities (e.g. Bein et al 2011;Cheng et al 2020;Patel et al 2021). Earlier studies have suggested that this main acceleration phase occurs at the lower coronal heights and hence might not be always captured using traditional white-light coronagraphic observations (Gallagher et al 2003;Temmer et al 2008;Majumdar et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…EUV coronal structures were also enhanced while reducing the dominance of noise based on a fuzzy algorithm (Druckmüller, 2013) and using Gaussian filtering for bringing out features at different scales (Morgan and Druckmüller, 2014). In another algorithm, CMEs Identification in Inner Solar Corona (CIISCO), a radial filter was applied on EUV images by dividing each individual image by a background uniform in azimuth direction generated using the radial intensity profile of the polar regions of the Sun (Patel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%